ENGLISH PRONUNCIATION BASED ON THE PHONETIC TRANSCRIPTION APPLICATION (STUDY OF TOPHONETICS.APP) - Yusuf, Faidah (Elite : English and Literature Journal, 2019)
This article is about English pronunciation based on the phonetics transcription Application (Study of tophonetics app). The aim of the article is focused to know English pronunciation based on the phonetics transcription by using tophonetics Application. The researcher used a descriptive qualitative method. The samples of this research are ten students, to look for the phonetics transcription by using tophonetics tools and to read the text of phonetics transcription. The writer used the interview as an instrument on this research was to collect the data. The result of this research that the pronunciation of phonetics transcription in English used tophonetics.app the students could be doing easy and understanding to use the app and could improve pronouncing the words better. Keywords: transcription, tophonetics, pronunciation, application, understanding ABSTRAK Penelitian ini untuk mengetahui bagaimana pelafalan bahasa Inggris berdasarkan transkripsi fonetik dengan menggunakan Aplikasi tophonetics. Peneliti menggunakan metode deskriptif kualitatif. Sampel penelitian ini adalah sepuluh siswa, untuk mencari transkripsi fonetik dengan menggunakan alat tophonetics dan membaca teks transkripsi fonetik. Penulis menggunakan wawancara sebagai instrumen dalam penelitian ini adalah untuk mengumpulkan data. Temuan dari penelitian ini adalah para mahasiswa mencari transkripsi fonetik dengan menggunakan aplikasi tophonetics ini. Hasil penelitian ini bahwa pelafalan transkripsi fonetik dalam bahasa Inggris menggunakan tophonetics. App, para mahasiswa yang membuatnya lebih mudah daripada membuka kamus, mereka dapat melakukan dengan mudah dan memahami untuk menggunakan aplikasi dan dapat meningkatkan pengucapan kata-kata yang lebih baik. Kata kunci: transkripsi, tophonetics, pengucapan, aplikasi, pemahaman